1997
DOI: 10.1007/pl00004965
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of cardiovascular histamine H1 receptor binding sites: characterisation with 2-phenylhistamines

Abstract: We determined and compared the molecular properties of histamine H1 receptor binding sites in bovine thoracic aorta smooth muscle and guinea pig myocardial membranes from ventricles with saturation and inhibition binding assay, using 3H-mepyramine to label the receptor and specific and selective H1 receptor agonists of the 2-phenylhistamine group as displacers of specific 3H-mepyramine binding. 3H-mepyramine binds in a saturable manner to a homogenous population of binding sites with a K(D) of 5.6 nM and a Bma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Specific binding represents the difference between total and non-specific binding (binding under the same incubation conditions as above, in the presence of 10 mM cimetidine), and represents 30 % of total binding (for details of binding assays see [31]). After incubation, the culture medium was collected, frozen and used for NGF determinations.…”
Section: Radioligand Binding Assaymentioning
confidence: 99%
“…Specific binding represents the difference between total and non-specific binding (binding under the same incubation conditions as above, in the presence of 10 mM cimetidine), and represents 30 % of total binding (for details of binding assays see [31]). After incubation, the culture medium was collected, frozen and used for NGF determinations.…”
Section: Radioligand Binding Assaymentioning
confidence: 99%
“…Bovine aorta smooth muscle cell membranes were prepared by adapting the method of Carman‐Krzan et al . (1997) and binding experiments were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…It seems clear that besides vasoconstriction, histamine H 1 receptors in the smooth muscle regulate many other understudied functional processes, such as mitochondrial function and gene transcription. Receptor binding studies have revealed histamine H 1 receptors in bovine aortic smooth muscle cells [ 139 ]. The vasoconstrictory effects of histamine H 1 receptor stimulation in rabbit coronary arteries were accompanied by a decrease in cAMP levels measured in these arteries [ 140 ].…”
Section: Histamine H 1 Receptor and Smooth Muscle ...mentioning
confidence: 99%